Prominently Portrayed? A Content Analysis Exploring Queer Representation in Food and Agriculture Magazines - Jarred A Shellhouse; Lauri Baker (Journal of Applied Communications, 2024)
Agriculture and food magazines share stories with readers that offer an insider perspective to the people and processes involved in getting food from farm to table. While queer issues have been long studied in the media, representation of queer people in stories has largely been missing from empirical research. This content analysis examined agriculture and food magazines for stories with queer representation to determine the framing, tone, and prominence of queerness in the articles. Articles were selected from the top ten agriculture magazines by circulation, and the top ten food magazines by circulation. Each of the 20 online magazine websites were searched for queer keywords, resulting in a sample of 72 articles from 2016-2022. Findings indicated most stories used a dominant equality/queer representation frame and discussed queerness in a positive or neutral tone. Both magazine types had a surge in publishing queer stories in a specific month of the year (June), but also in the most recent year (2022). Additionally, findings indicated food magazines are more likely than agriculture magazines to use queer words or symbols in the headline, subhead, images, or image captions. Implications exist for shaping the culture and representation of queer stories in agriculture and the food system, and agricultural communicators who want to include queer perspectives and voices.